Taxpayer Responses to Competitive Tax Policies and Tax Policy Responses to Competitive Taxpayers : Recent Evidence - Rosanne Altshuler; Harry Grubert (Rutgers University, Department of Economics, 2004)
We use information from the tax returns of U.S. multinational corporations to address three questions related to tax competition. First, does tax competition or company tax planning behavior better explain recent decreases in the local effective tax rates faced by U.S. multinationals investing abroad? Second, have countries become more aggressive in their use of tax concessions to attract particular types of foreign capital? And finally, has the role of taxes in the location decisions of U.S. manufacturers increased in recent years? Between 1992 and 2000, the average effective tax rate faced by U.S. manufacturers on income earned abroad fell from 25 percent to 21 percent. Our results suggest that the evolution of country effective tax rates between 1992 and 1998 seems to be driven by tax competition. Countries that lost shares of U.S. manufacturing real capital prior to 1992 cut their rates the most over this period. However, the most recent data suggests that companies may not need tax competition to lower effective tax burdens abroad. The evolution of country effective rates between 1998 and 2000 seems to be driven by company rather than country behavior. This is consistent with the introduction of the ?check the box? regulations in 1997 which made it easier for corporations to use ?self-help? to lower tax burdens. Interestingly, we find that countries were rewarding more mobile companies and those that were perceived to be more beneficial to the local economy with tax concessions as far back as 1984. Finally, although not conclusive, our empirical work suggests that U.S. manufacturers may have become more sensitive to differences in local tax rates across countries in recent years.
Keywords: 330; Steuerwettbewerb; Steuerpolitik; Multinationales Unternehmen; Betriebliche Standortwahl; Steuerbelastung; Vereinigte Staaten; Welt